Computational tools for genomic data de-identification: facilitating data protection law compliance - Alexander Bernier (Nature Portfolio, 2021)
In this opinion piece, we discuss why computational tools to limit the identifiability of genomic data are a promising avenue for privacy-preservation and legal compliance. Even where these technologies do not eliminate all residual risk of individual identification, the law may still consider such data anonymised.